Application of IOT technology in providing population health during the Sars-Cov-2 pandemic - Dalibekov Lochinbek Rustambekovich; Ergashev Shohbozjon Umarali o’g’li; Orifjonova Durdona Vohidjon qizi (International Journal of Human Computing Studies, 2020)
This article discusses the possibilities of using smart solutions in order to increase the efficiency of the medical system. During the SARS-CoV-2 pandemic, the possibility of remote online monitoring of the health of patients with chronological disease will be considered in order to prevent them from becoming infected with the virus. The use of IoT technology in the organization of a medical system with this potential will be considered.